Environmental risks of thermal waste management and prospects for sustainable remediation - Soboliev, Serhii; Pitak, Inna (Ivano-Frankivsk National Technical University of Oil and Gas, 2025)
Th management of municipal solid waste remains one of the most urgent environmental challenges in Ukraine, particularly in the Kharkiv Region, where soil contamination and groundwater vulnerability intensify ecological risks. Th study aimed to assess the environmental risks of thermal waste treatment technologies in the Kharkiv Region and evaluate their compatibility with ecosystem restoration strategies. Th research applied a comparative analytical approach, integrating environmental impact assessment methods to analyse incineration, pyrolysis, and plasma gasifiation technologies. Th assessment included estimation of pollutant emissions, energy effiency, and secondary waste formation under regional conditions. It has been established that incineration, while effctive at reducing waste volume, produces hazardous residues containing heavy metals and organic toxins. Pyrolysis demonstrates lower emissions and produces biochar capable of immobilising pollutants in soils, thereby enhancing its potential integration with phytoremediation practices. Plasma gasifiation provides nearly complete decomposition of complex waste streams, but it demands a high energy input and advanced technical infrastructure. Th study identifid that, under the post-conflct context of the Kharkiv Region, pyrolysis offrs the best balance between environmental safety and resource effiency. A framework for integrating thermal treatment residues into soil recovery strategies has been developed to support regional sustainability. Th results can be applied by environmental engineers, municipal authorities, and policymakers to design sustainable waste-to-energy systems adapted to environmentally sensitive and post-conflct areas.

Управління твердими побутовими відходами залишається однією з найгостріших екологічних проблем в Україні, особливо в Харківській області, де забруднення ґрунтів і вразливість підземних вод посилюють екологічні ризики. Метою дослідження було оцінити екологічні ризики технологій термічної обробки відходів у Харківській області та визначити їхню сумісність зі стратегіями відновлення екосистем. У роботі застосовано порівняльний аналітичний підхід із інтеграцією методів оцінки впливу на довкілля для аналізу технологій спалювання, піролізу та плазмової газифікації. Оцінювання включало визначення викидів забруднювальних речовин, енергоефективності та утворення вторинних відходів з урахуванням регіональних умов. Встановлено, що спалювання, хоча й ефективно зменшує об’єм відходів, утворює небезпечні залишки, які містять важкі метали та органічні токсини. Піроліз характеризується нижчими рівнями викидів і утворенням біочару, здатного іммобілізувати забруднювачі в ґрунтах, що підвищує його потенціал інтеграції з практиками фіторемедіації. Плазмова газифікація забезпечує майже повне розкладання складних потоків відходів, однак потребує значних енергетичних витрат і розвиненої технічної інфраструктури. Дослідження показало, що в умовах післяконфліктного контексту Харківської області піроліз забезпечує найкращий баланс між екологічною безпекою та ресурсною ефективністю. Розроблено підхід до інтеграції залишків термічної обробки у стратегії відновлення ґрунтів з метою підтримки регіональної сталості. Отримані результати можуть бути використані інженерами-екологами, органами місцевого самоврядування та політиками для проєктування сталих систем перетворення відходів на енергію, адаптованих до екологічно чутливих і післяконфліктних територій.
Екологічні ризики термічного управління відходами та перспективи сталого відновлення
Keywords: waste-to-energy technologies; pollutant emissions; soil and water protection; ecosystem restoration; resource effiency; sustainable recovery; технології перетворення відходів на енергію; викиди забруднювальних речовин; охорона ґрунтів і вод; відновлення екосистем; ресурсна ефективність; сталий розвиток